POLAND’S FOREIGN POLICY CONCEPTS TRADITIONS AND INNOVATIONS REGARDING UKRAINE (the XXth – the beginning of the XXIst century) - Dobrzhanskiy, Oleksander; Strilchuk, Lyudmyla (Видавничий дім «Гельветика», 2021)
In the modern world, the state’s foreign policy is one of the supporting foundations of statehood, and therefore the study of the foreign policy concepts formation and implementation experience is relevant and necessary for the development of the modern interstate and good neighborly relations between Ukraine and Poland. The Polish political elite, in different historical periods, distinguished visions about Ukraine clearly, its role and significance for Rzeczpospolita (Commonwealth), and these visions remained constant, actualized over time, or, conversely, acquired new shapes and coloring. The Piast and the Jagiellonian concepts have been the main Poland’s foreign policy concepts since the beginning of the XXth century, and continue to be of utmost importance and that new or existing foreign policy doctrines have been created or developed based on them. The article depicts Poland’s foreign policy concepts evolution regarding Ukraine, in particular, and the eastern vector of Polish politics in general. The purpose of the research is to analyze and compare Poland’s foreign policy concepts evolution towards Ukraine and to study the factors that influenced the transformation of these concepts.
Keywords: Poland, Ukraine, foreign policy, Jagiellonian concept, Piast concept, Prometheanism, incorporation, eastern policy.